2016
DOI: 10.1021/acsami.5b11810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interfacial Bonding on Interphase Properties in SiO2/Epoxy Nanocomposite: A Molecular Dynamics Simulation Study

Abstract: Atomistic molecular dynamics simulations have been performed to explore the effect of interfacial bonding on the interphase properties of a nanocomposite system that consists of a silica nanoparticle and the highly cross-linked epoxy matrix. For the structural properties, results show that interfacial covalent bonding can broaden the interphase region by increasing the radial effect range of fluctuated mass density and oriented chains, as well as strengthen the interphase region by improving the thermal stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 61 publications
0
81
0
Order By: Relevance
“…The results indicate that the aminosilane coupling agents could improve the thermal properties of the cross-linked epoxy resin. In some examples within the literature [9,11,32,33,34], the glass transition temperature shifted T g from 400 K to 483 K. Different epoxy resin monomers, curing agents, and experimental conditions make the T g different to some extent, which indicates that the simulation in this paper has certain reliability.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The results indicate that the aminosilane coupling agents could improve the thermal properties of the cross-linked epoxy resin. In some examples within the literature [9,11,32,33,34], the glass transition temperature shifted T g from 400 K to 483 K. Different epoxy resin monomers, curing agents, and experimental conditions make the T g different to some extent, which indicates that the simulation in this paper has certain reliability.…”
Section: Resultsmentioning
confidence: 83%
“…The pure epoxy resin model, the EP/SiO 2 composite model (the surface of SiO 2 without any modifier), and surface of the silica respectively grafted with epoxy resin doped with 3-aminopropyltriethoxysilane (A1100), N -(2-aminoethyl)-3-aminopropyltrimethoxysilane (A1120), and 3-[2-(2-aminoethylamino)ethylamino (A1130) were built, which were represented as pure, SiO 2 , A1100, A1120, and A1130. In this paper, COMPASS [11,14,15,16,17,18] was selected as the force field for calculations in all dynamic simulations; Nose [18] and Berendsen [19] were used for temperature control and pressure control, respectively. Figure 1 shows the SiO 2 composites and the pure epoxy resin model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the direct numerical resolution of thin layers with continuum-based standard finite element or boundary element methods requires prohibitively fine mesh sizes [8]. On the other hand, molecular dynamics type approaches are often prohibitively expensive for sample sizes and at scales of engineering interest [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the chemical bond in the interface region can increase the glass transition temperature of the epoxy resin by 21 K when the graft ratio exceeds 5.8%, which enhances the thermal conductivity of the composite model. In the meanwhile, the interfacial chemical bond can reduce the mobility of epoxy resin molecular chains [23]. Wang Y simulated the interfacial thermal resistance and thermal conductivity of SrTiO 3 particles, showing that the size of the nanoparticles is closely related to the thermal conductivity [24].…”
Section: Introductionmentioning
confidence: 99%